Investigation of the spastin's role in the invasion capacity of glioblastomas - İmanç Temizci, Benan (Graduate School, 2024)
Glioblastoma Multiforme (GBM) is the most lethal form of glioma, which are the most frequent brain tumors. Even though multimodal therapy is employed to treat GBM, tumor recurrence makes treatment almost impossible due to its robust migration/invasion potential. For the improvement of GBM therapy, it is critical to identify the proteins involved in the disease's migration/invasion process. Tumor cells require special cellular extensions controlled by cytoskeletal components to achieve migration/invasion capabilities. Spastin, a microtubule-severing protein, is mainly expressed in neurons and controls dendrites and axonal extensions of neurons. Given that the formation mechanism of these extensions in post-mitotic cells is comparable to that of specialized cell protrusions in mitotic cells, Spastin might have roles in tumor cell migration/invasion. Interestingly, Spastin has been discovered to be co-localized with actin filaments in GBM cells, suggesting that it may play a role in GBM migration ability. However, this topic has not been investigated in the literature until this study. This thesis aims to clarify the molecular mechanism underlying the shift in the intracellular localization of Spastin in GBM cells, and the potential significance of this mechanism in GBM migration/invasion ability. This study discovered for the first time that Spastin takes an active role in GBM migration. Furthermore, Spastin was discovered to interact with Pin1 via phosphorylation of Pin1 recognition motifs located in its microtubule-binding domain. Moreover, this interaction was found to direct of Spastin towards actin filaments, which promotes migration/invasion ability of GBM cells. These findings suggest that Spastin might be a therapeutic target for several tumors with a high migration/invasion capacity, like GBM.
Glioblastomaların invazyon kapasitesinde spastin'in rolünün incelenmesi
Thesis (Ph.D.) -- Istanbul Technical University, Graduate School, 2024
Keywords: Cytoskeleton; Hücre İskeleti; Neoplazm hücreler; Neoplastic cells